(untitled) (Annals of Medical Research, 2021)
Aim: This study aimed to investigate histomorphological changes in cardinal ligaments between patients with and without uterine prolapse.Material and Methods: This study included 30 patients who underwent vaginal hysterectomy for POP-Q stage 4 uterine prolapse (Group 1) and 30 patients who underwent abdominal hysterectomy for benign reasons except uterine prolapse (Group 2) at a tertiary center hospital. Demographic data, parity, uterine weight, and histomorphological findings of cardinal ligaments were compared between the two groups.Results: Age and parity were significantly higher unlike uterine weight was lower in Group 1. In histomorphological findings of cardinal ligaments, vessel wall thickness, peripheral nerve thickness and the number of cells in the connective tissue stroma counted in 1 mm2 area were statistically significantly higher in Group 1. While the presence of extravasated erythrocytes was greater in Group 1, no significant difference was found between the two groups in terms of inflammation.Conclusion: It is obvious that some histomorphological changes are formed in the cardinal ligaments of patients with uterine prolapse due to pressure on the uterus. We believe that the increase in the number of extravasated erythrocytes and the thickness of the vascular wall and peripheral nerve should be supported by further studies.